Identification of Plasmodium falciparum and host factors associated with cerebral malaria: description of the protocol for a prospective, case-control study in Benin (NeuroCM) - Valentin Joste; Laurine Maurice; Gwladys I Bertin; Agnès Aubouy; Farid Boumédiène; Sandrine Houzé; Daniel Ajzenberg; Nicolas Argy; Achille Massougbodji; Ida Dossou-Dagba; Maroufou Jules Alao; Michel Cot; et al. (BMJ Open)
Introduction In 2016, an estimated 216 million cases and 445 000 deaths of malaria occurred worldwide, in 91 countries. In Benin, malaria causes 26.8% of consultation and hospitalisation motif in the general population and 20.9% in children under 5 years old.The goal of the NeuroCM project is to identify the causative factors of neuroinflammation in the context of cerebral malaria. There are currently very few systematic data from West Africa on the aetiologies and management of non-malarial non-traumatic coma in small children, and NeuroCM will help to fill this gap. We postulate that an accurate understanding of molecular and cellular mechanisms involved in neuroinflammation may help to define efficient strategies to prevent and manage cerebral malaria.Methods and analysis This is a prospective, case-control study comparing cerebral malaria to uncomplicated malaria and non-malarial non-traumatic coma. This study takes place in Benin, precisely in Cotonou for children with coma and in Sô-Ava district for children with uncomplicated malaria. We aim to include 300 children aged between 24 and 71 months and divided in three different clinical groups during 12 months (from December 2017 to November 2018) with a 21 to 28 days follow-up for coma. Study data, including clinical, biological and research results will be collected and managed using CSOnline-Ennov Clinical.Ethics and dissemination Ethics approval for the NeuroCM study has been obtained from Comité National d’Ethique pour la Recherche en santé of Benin (n°67/MS/DC/SGM/DRFMT/CNERS/SA; 10/17/2017). NeuroCM study has also been approved by Comité consultatif de déontologie et d’éthique of Institut de Recherche pour le Développement (IRD; 10/24/2017). The study results will be disseminated through the direct consultations with the WHO’s Multilateral Initiative on Malaria (TDR-MIM) and Roll Back Malaria programme, through scientific meetings and peer-reviewed publications in scientific or medical journals, and through guidelines and booklets.